Examining the Effects of Robotic Process Automation on Operational Efficiency and Business Process Optimization (Literature Study) - Legito (Westscience Press, 2023)
This research study investigates the influence of Robotic Process Automation (RPA) on operational efficiency and business process optimization. The study adopted a systematic literature review approach to collect and analyze relevant academic articles, industry reports, and conference proceedings. Findings reveal that RPA implementation significantly improves operational efficiency by automating repetitive and rule-based tasks. This automation reduces manual effort, minimizes errors, and speeds up process execution, leading to increased productivity, faster response times, and cost savings for organizations. RPA also contributes to business process optimization by streamlining workflows, eliminating bottlenecks, and standardizing processes. Standardized execution of tasks through RPA improves process efficiency, quality, and visibility, allowing organizations to make data-driven decisions and continuously optimize their operations. However, challenges such as process complexity, employee resistance to change, integration issues, and data security concerns need to be addressed for a successful RPA implementation. Organizations must develop a comprehensive implementation plan, establish a governance framework, and foster a culture of collaboration to overcome these challenges. The practical implications derived from this research offer guidance for organizations that are considering or implementing RPA solutions. Recommendations include conducting a thorough process analysis, developing a comprehensive implementation plan, establishing governance mechanisms, encouraging collaboration, and continuously optimizing processes. While this study provides valuable insights into the impact of RPA on operational efficiency and business process optimization, it acknowledges the limitations of the research, such as the reliance on literature up to September 2021 and the subjectivity of the data analysis.